Publishing in the Majors: A Comparison of Accounting, Finance, Management, and Marketing* - SWANSON, EDWARD P. (Contemporary Accounting Research, 2004)
Abstract Business schools evaluate publication records, especially for the promotion and tenure decision, by comparing the quality and quantity of a candidate's research with those of peers within the same discipline (intradisciplinary) and with those of academics from other business disciplines (interdisciplinary). A recently developed analytical model of the research review process provides theory about the norms used by editors and referees in deciding whether to publish research papers. The model predicts that interdisciplinary differences exist in quality norms, which could result in disparity among business disciplines in the number of top‐tier articles published. I examine the period from 1980 to 1999 and, consistent with the theory, find that significant differences exist in the number of articles and proportion of doctoral faculty who published in the “major” journals in accounting, finance, management, and marketing. Most notably, the proportion of doctoral faculty publishing a major article is 1.4 to 2.4 times greater in the other business disciplines than in accounting (depending on the set of journals). The theory also predicts an upward drift over time in the quality norms used by referees. Consistent with a drift, the number of articles published has declined substantially in marketing and, to a lesser extent, in the other business disciplines.